PENGARUH STRUKTUR ASET DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PT. SEPATU BATA TBK - Nurwahidatun, Nurwahidatun; Huda, Nurul (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2023)
This study aims to analyze the effect of asset structure and sales growth on the capital structure of PT Sepatu Bata Tbk. This type of research is associative which aims to determine the effect or relationship between two or more variables. The analytical tools used are distance analysis, growth analysis, der analysis, classical assumption analysis, normality analysis, autocorrelation analysis, multiple linear analysis, t test and f test (SPSS Version 21). The results of this study indicate that asset structure has no effect on capital structure and sales growth has a negative and significant effect on capital structure. To improve the capital structure, namely by reducing long-term debt, and increasing sales so that the capital structure will be more stable and optimal.